Vulnerabilidade de consumo e os serviços financeiros : as condutas e percepções dos agentes bancários frente ao bem-estar financeiro dos indivíduos - Basílio, Roberta Gabriela (2019)
Financial services companies are under internal pressure to maximize results at the lowest possible cost, external pressure from society and legislation to act ethically. Nonetheless, the two largest Brazilian retail banks lead the unmet complaints ranking in Procon. Approximatelly 35% of Brazilian adults lack financial education. This means that even though the consumer is exposed to credit supply they have no adequate knowledge to ensure their financial well being. Based on the concepts of financial well-being, consumer vulnerability and ethical sales decision-making, this study proposes to understand the meanings of banking agents' behaviors and perceptions regarding consumer financial well-being addressingthe ethical dilemmas involved in financial services offerings We conducted 12 in-depth interviews with baking agents in charge of activities related to offering financial products to potential customers. We submitted the research information to a content analysis using a phenomenological approach to explore the experiences of these banking agents. The analysis of the interviews presents three themes, which involve the interactions between sellers and the consumers’ well-being, as well as the ethical dilemmas they face in the provision of financial services. Conflict of interest is the main dilemma they encounter in their activities. Results suggest that in the face of the customers' well-being, the agents act in two conflicting behaviors: pressured by their sales targets, they can influence vulnerable consumers to opt for financial decisions that are not fit for them. This study aims to identify situations of financial exploitation from the perspective of banking agents. Furthermore, we hope to extend the literature on the influence of financial services on customers’ well being, revealing practices of Brazilian retail banking. We also present Managerial implications and suggestions for future research.